Health Disparities in the Immunoprevention of Human Papillomavirus Infection and Associated Malignancies - Bakir, Amira H.; Skarzynski, Martin (Frontiers in Public Health, 2015)
Human papillomavirus (HPV) causes about 1.6% of the roughly 1.6 million new cancer cases that are diagnosed in the United States each year. Despite the proven safety and efficacy of currently available vaccines, HPV remains the most common sexually transmitted infection. Underlying the high prevalence of HPV infection is the poor adherence to the Centers for Disease Control (CDC) recommendation that all 11-12 year old males and females be vaccinated. In fact, only about 38% and 14% of eligible females and males respectively, receive the complete, three-dose immunization. Many factors are associated with missed HPV vaccination opportunities, including race, age, family income and patient education, resulting in widespread disparities in vaccination rates and related health outcomes. Beyond patient circumstance, however, research indicates that the rigor and consistency of recommendation by primary care providers also plays a significant role in uptake of HPV immunization. Health disparities data are of vital importance to HPV vaccination campaigns because they can provide insight into how to address current problems and allocate limited resources where they are most needed. Furthermore, even modest gains in populations with low vaccination rates may yield great benefits because HPV immunization has been shown to provide herd immunity, indirect protection for non-immunized individuals achieved by limiting the spread of an infectious agent through a population. HPV vaccination campaigns face the challenge of stagnant HPV immunization rates, which are increasing slowly overall but remain far below target levels. Furthermore, gains in immunization are not equal across all groups and vaccination rates are strikingly disparate across the federal poverty level. To achieve the greatest impact, public health campaigns should focus on improving vaccination coverage where it is weakest. In addition to demographics, socioeconomic factors and attitudes of parents, children and healthcare providers, vaccination efforts should take into account disparities in the of prevalence of factors that can exacerbate HPV-related health outcomes such as smoking and human immunodeficiency virus-mediated immunosuppression. Optimizing the efficacy of vaccination campaigns will require a health disparities approach that identifies and remedies the underlying causes of population differences in HPV vaccination.